PENGARUH UKURAN PERUSAHAAN DAN PERTUMBUHAN PERUSAHAAN TERHADAP OPINI AUDIT GOING CONCERN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ainoriastiti, Winda (JEM17: Jurnal Ekonomi Manajemen, 2018)
This study aims to find out: (1) Effect of company size on profitability; (2) Effect of company growth on profitability; (3) Effect of company size on going- concern audit opinion; (4) Effect of profitability on going-concern audit opinion; (5) Effect of company growth on going- concern audit opinion. This research uses descriptive quantitative. The population in this study is the food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange in 2015-2017. Data collection techniques using purposive sampling. Samples used in this study were 14 companies from 22 companies registered in 2015-2017. Data analysis techniques use Partial Least Square (PLS). Based on the results of the study show that: (1) The size of the company has a positive and significant effect on profitability. This is indicated by the value of T- statistics of 4.407 (>1.97) and the original sample value of 0.509; (2) Company growth has a negative and not significant effect on profitability with a T-statistic value of 0.698 (<1.97) and an original sample value of 0.0611; (3) The size of the company has a positive and significant effect on the going concern audit opinion with a T-statistic value of 2.484 (> 1.97) and the original sample value of 0.388; (4) The growth of the company has a negative effect and is not significant towards the going concern audit opinion with the value of T-Statistics of 0.437 (<1.97) and the original sample value of -0.0554; (5) Profitability has a negative and significant effect on going-concern audit opinion with a T-statistic value of 3.328 (> 1.96) and an original sample value of -0.576.Kata Kunci : Going Concern Audit Opinion, Profitability, Company Size, and Company Growth.